ANALISIS DUKUNGAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI SMK IMMANUEL II - Jeremia, Abisai; Matsum, Junaidi H; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study was conducted at SMK Immanuel II Kubu Raya. The purpose of this study was to find out if school culture supports the performance of teachers in SMK Immanuel II. The research model used in this work is a descriptive qualitative study. The informants for this study consisted of three economics teachers. The data collection techniques used in this study were interview, observation and documentation methods. The results of this study show the support of school culture for teacher performance. The teachers of this school receive support in their work in the form of good habits, for example, the skill of teachers in dealing with existing teaching materials. The school culture here also supports teachers to become better personalities and also to take responsibility for their work. The researcher's advice to teachers is that by applying the existing culture, the teacher becomes a respected person both in the school environment and in the wider community.